Disguised Resistance of Madurese Salt Farming Community - Iskandar Dzulkarnain; Endriatmo Soetarto; Rilus A. Kinseng; Sofyan Sjaf (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2020)
The problems of Madurese salt farmers, ranging from poverty, quality of production, low salt prices, to 'seizure' of the lands by Dutch Colonialism through the total reorganization program in 1936 as well as the project of modernization and renovation of the New Order regime in 1975 have become the triggers of the resistance put up by the salt farming community. The purpose of this article is to picture out the dynamics of the resistance by Madurese salt farming community through the theoretical analysis of James Scott, namely the daily resistance by Madurese salt farming community, which the writer -in other words- say 'disguised resistance'. The method used is qualitative with an ethnographic approach. The result is that there are two forms of disguised resistance put up by the Madurese salt farming community i.e. the resistance against PT. Garam and the resistance against the land ownres.